Influence of punitive populism on the legal practice - Chiroque Bances, María Dolores (2022)
This article shows us that punitive populism is a mechanism that the on-duty lawmakers use to offset the suffering of the citizenry affected by social conflicts, public insecurity and criminality. To this effect, they take the criminal code and dictate laws increasing the punishment, life imprisonment and eliminating procedural and prison benefits, particularly in high profile mainstream media cases: sexual abuse of minors, without taking into account the real problems and the fundamental rights of the criminal, but only the suffering of the victim. In view of the foregoing, this article attempts to establish parameters for those responsible for the administration of justice, who must be duly knowledgeable and trained in constitutional law and no longer be the mouth of the law, since this mechanism is proving to be having negative effects resulting in the overcrowding of penitentiaries.